Methodik für Erfassung und Bewertung von emotionalem Kundenfeedback für variantenreiche virtuelle Produkte in immersiver Umgebung - Katicic, Jurica (Reihe Informationsmanagement im Engineering Karlsruhe / Hrsg.: Karlsruher Institut für Technologie, Institut für Informationsmanagement im Ingenieurwesen (IMI), 2013)
This work describes a methodology for customer-centered selection of solutions for future product in the concept stage using their virtual representation. It integrates the technology of Virtual Reality and the emotions research into the parallel and interdependent processes of product development and market research, in order to enable the acquisition of relevant emotional feedback during interactive product experiencing.